ROLE OF COMMUNICATION TOOLS IN THE PROMOTION OF MUSIC: संगीत के प्रचार-प्रसार में संचार साधनों की भूमिका - Rao, Neeraj (International Journal of Research -GRANTHAALAYAH, 2015)
Music has been a means of entertainment and fun for human beings since time immemorial. Since ancient times, humans have used various types of means for their entertainment, as the human developed his civilization, his understanding and understanding attracted him to dance, singing and playing. Humans learned music by understanding civilization and culture while harmonizing themselves with nature. It is also mentioned in our mythological texts that, seeing the singing posture of Maa Parvati, Lord Shankar composed five ragas Hindol, Deepak, Shree, Megha, Kaushik etc., and the origin of music of Lord Shiva's Tandava and Mother Parvati. The target assumed dance. In this way the rhythm of the "Ta" of the Tandava, and "L" of Lasya were formed by these two words. मनुष्य को आदिकाल से ही संगीत मनोरंजन एवं आमोद-प्रमोद का साधन रहा है। आदिकाल से ही मानव ने अपने मनोरंजन के साधन के लिये विभिन्न प्रकार के प्रयोग किये जैसे-जैसे मानव अपनी सभ्यता का विकास करता गया वैसे-वैसे उसकी समझ और सूझ-बूझ ने नृत्य, गायन और वादन की ओर आकर्षित किया। मानव ने सभ्यता और संस्कृति को समझकर अपने को प्रकृति के साथ तालमेल करते हुए संगीत को सीखा। हमारे पौराणिक ग्रंथों में भी इस बात का उल्लेख है कि माँ पार्वती की गायन मुद्रा को देखकर भगवान षंकर ने क्रमषः पाँच राग हिंडोल, दीपक, श्री, मेघ, कौषिक आदि रागों की रचना की एवं संगीत की उत्पत्ति भगवान षिव के ताण्डव तथा माता पार्वती के लक्ष्य नृत्य से मानी गई। इस प्रकार ताण्डव के ‘‘ता’’’, और लस्य के ‘‘ल‘‘ इन दो षब्दों से ताल का निर्माण हुआ।